Corruption, Informality and Entrepreneurship in Romania - Bratu, Roxana (Political Corruption and Governance, 2018)
This book examines the meaning, structure, practices and symbolism of corruption in relationship to European Union structural funding in Romania. It offers a unique account of the complex transformations faced by post-communist societies. Despite the new legislation that effectively re-branded typical economic practices in Romanian society as 'corruption', entrepreneurs continue to use them in everyday interactions. The entrepreneurial culture described in the chapters is an ordinary trait of the local work routines. Rather than pursuing the singular logic of corruption, the author explores the concept of informality by focusing on the socio-historical context and the meanings embedded in the society that provides solutions to the problems. The book will appeal to students, scholars and practitioners in the areas of corruption, public policy and EU policy and politics.